Alexandrite Lasers: Review of recent laser progress and developments for vegetation lidar - Damzen Michael J. (EPJ Web of Conferences)
A review is made of recent progress in diode-pumped Alexandrite lasers as a high-power, tunable- wavelength source, and our advances in developing Alexandrite as a short-pulse, high-pulse-rate vegetation lidar source for satellite-based Earth Observation.